Gender differences in one‐year outcomes of first‐presentation psychosis patients in inner‐city UK Early Intervention Services. Issue 3 (23rd March 2015) - Tseliou, Foteini; Johnson, Sonia; Major, Barnaby; Rahaman, Nikola; Joyce, John; Lawrence, Jo; Mann, Farhana; Tapfumaneyi, Andrew; Chisholm, Brock; Chamberlain‐Kent, Nick; Hinton, Mark F.; Fisher, Helen L.; et al.
Abstract: Aim: Men and women have historically been shown to differ in their presentation and outcome of psychotic disorders and thus are likely to have different treatment needs. It is unclear whether Early Intervention Services (EIS) are able to provide equitable care for both men and women presenting for the first time with psychosis. The main aim of this study was to explore gender differences for first‐presentation psychosis patients at the time of their referral to inner‐city EIS and their outcomes 1 year later. Methods: Audit data were utilized from 1098 first‐presentation psychosis patients from seven EIS across London, UK, collected via the computerized MiData package. Binary logistic regression was employed to detect potential associations between gender and (i) initial clinical presentation (including duration of untreated psychosis, pathways to care, risk behaviours); and (ii) 1‐year clinical and functional outcomes. Results: At entry to EIS, male patients presented with more violent behaviour whereas female patients had more suicide attempts. Following 1 year of EIS care, men still presented as more violent towards others whereas women were more likely to have been admitted to a psychiatric ward. Conclusion: Gender differences in clinical outcome, service use and risk behaviours were apparent within the first year of specialist psychosis care. This may be partly due to the different pathways to care taken by men and women and differences in clinical presentation. Greater focus on the specific needs of each gender by EIS in detection and intervention is required to improve equality of outcome.